2022
DOI: 10.1021/acsomega.1c07242
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of a Novel Nanocomposite Particle Gel for Water Shutoff Treatment in Mature Oilfields

Abstract: Conventional preformed particle gels suffer from insufficient salt tolerance and weak mechanical properties after water absorption, which reduce the water shutoff effect in mature oilfields. In this paper, a nanocomposite particle gel (NCPG) is synthesized by copolymerization of acrylamide (AM) and 2-acrylamido-2-methylpropane sulfonic acid (AMPS) using laponite RD (LPT) as a physical cross-linker and N,N-methylene-bisacrylamide (MBA) as a chemical cross-linker via in situ free radical polymerization. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, increasing the temperature and the thermal hydrolysis beyond the optimum conditions will open up more of the 3D network structure, leading to losses in the polymer chain's connections and, thus, less water loss or syneresis and a lower swelling ratio [14]. Contrary to others, PAM6.5%/Cs0.25% is most susceptible to polymer chain ruptures and syn- When comparing the behavior of PAM/Cs PPG in saline conditions with other PPG systems in the literature [17,23,25,42], one can notice their good behavior in terms of swelling capacity and ultimate strength, besides their non-toxicity property. In HSW, the TDS of 67.2976 g/L, the swelling ratios of PAM/Cs vary from 12.22 to 18.73 g/g, and the strengths are from 2052.9 to 5980.2 Pa.…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing the temperature and the thermal hydrolysis beyond the optimum conditions will open up more of the 3D network structure, leading to losses in the polymer chain's connections and, thus, less water loss or syneresis and a lower swelling ratio [14]. Contrary to others, PAM6.5%/Cs0.25% is most susceptible to polymer chain ruptures and syn- When comparing the behavior of PAM/Cs PPG in saline conditions with other PPG systems in the literature [17,23,25,42], one can notice their good behavior in terms of swelling capacity and ultimate strength, besides their non-toxicity property. In HSW, the TDS of 67.2976 g/L, the swelling ratios of PAM/Cs vary from 12.22 to 18.73 g/g, and the strengths are from 2052.9 to 5980.2 Pa.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Nevertheless, polyacrylamide, polyacrylic acid, and the co-polymer combining are the most abundant. Typically, organic crosslinkers such as N, N-methylene bis-acrylamide [18,23,24] or inorganic crosslinkers [14,25] are utilized in the process of PPG's production. Some PPGs share formulations or crosslinkers with those used in the in-situ gels, such as polyethylenimine [19], chromium acetate [25], and aluminum nitrate [14], which indicates that the formulations of the current in-situ gels might also develop PPGs for water shut-off treatment, having the advantage of being PPG.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to an earlier equilibrium state with a lower swelling ratio than freshwater. Parallel studies have verified that utilizing saline solutions as swelling media decelerates the PPG swelling rate. Moreover, the quicker swelling kinetics of AlLc PPG, as observed in freshwater and seawater, can be attributed to its denser network structure than others. This increased density restricts water inflow, facilitating the faster attainment of its equilibrium swelling capacity.…”
Section: Results and Discussionmentioning
confidence: 87%
“…It can be observed that the degradation temperature of the NR-PPG sample is shifted toward a higher temperature when compared to the WR-PPG sample. 33,51 Furthermore, the DTG graph (Figure 14) shows that the highest loss for WR-PPG was recorded at 371 °C. In contrast, a similar type of deterioration peak was found for the NR-PPG sample at 377 °C.…”
Section: Fesem Analysismentioning
confidence: 99%